The Effect of Fiscal Decentralization and Foreign Direct Investment on Regional Income Inequality: Economic Growth as A Mediating Variable - Triyono Triyono; Dwi Ariyani; Noer Sasongko (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims analyzed the effect of Fiscal Decentralization and Foreign Direct Investment (FDI) on regional income inequality and examined the role of economic growth in the relationship of independent variables with income inequality in Indonesia. The analytical tool used path analysis (Path Analysis). The sample 34 provinces in Indonesia from 2015-2019. The results showed (1) fiscal decentralization has a significant negative effect on economic growth in Indonesia in 2015-2019. (2) FDI has a significant positive effect on economic growth. (3) Fiscal decentralization has a significant positive effect on income inequality. (4) FDI didn’t effect on income inequality. (5) Economic growth has a significant positive effect on income inequality. (6) Economic growth isn’t able to mediate fiscal decentralization on regional income inequality. (7) Economic growth is able to mediate FDI on regional income inequality.